Crashes and other safety-related incidents in the formation of attitudes toward bicycling. (January 2015) - Lee, Amy E.; Underwood, Sarah; Handy, Susan
Highlights: The greater the severity of injuries, the greater the impact on attitudes toward bicycling. Crashes in adulthood negatively affected attitudes but crashes in youth did not. Incidents involving motorists had more impact than solo crashes. Crashes by others negatively affected attitudes especially for infrequent bicyclists. Liking of biking moderated the emotional response to crashes. Abstract: Many cities are encouraging bicycling as mode of transportation as a way to improve air quality and health. Evidence suggests a strong influence of attitudes on bicycling, but few studies have examined the formation of attitudes toward bicycling. This paper explores the potential effect of crashes and other incidents on attitudes towards bicycling. Several themes emerge from 54 in-depth interviews on experiences with bicycling over the life course for a sample of adults living in Davis, California. The greater the severity of injuries associated with a crash, the greater the likelihood of declines in comfort with and desire for bicycling. Crashes in youth had very little effect on desire for or comfort with bicycling, but the opposite was true of crashes in adulthood. Incidents involving motorists particularly exacerbated discomfort with bicycling, while solo crashes were commonly perceived as unlucky or careless mishaps. Crashes experienced by others, as opposed to those experienced personally, were especially damaging to attitude, particularly for those who did not bicycle regularly. These findings have important implications for the design of bicycle facilities and programs.